Formation of statistical indicators system to create objects of the primary real estate market - D. V. Dianov (Статистика и экономика, 2020)
The analytical value of the complex system of statistical indicators characterizing the creation of value in the primary real estate market is determined by the sensitivity of the entire socio-economic sphere to the object of study, since it is the population, that is, the end user of this element of national accumulation, feels it as a factor of living standards, welfare, material potential and even as the possibility of obtaining passive income in the form of property rent.The secondary market of residential real estate, where a huge share of cash savings of the population turns out, is partly inferior in its importance to the primary market. This applies to the fact that the primary market is the relationship of the subjects about not only the movement, but also the creation of value. Thus, we are talking about the circulation of tangible assets, which are an integral part of the new, newly created gross domestic product, namely that part of it that is not consumed as part of final consumption, but represents gross capital formation – the accumulation of fixed capital.Purpose. Presentation of statistical methodology content, relating to the language of any statistical study – indicators, in this case the systematization and ordering of a comprehensive system of indicators of statistics of the creation of objects in the primary real estate market.Materials and methods. Since the article is of a methodological nature, it uses the methods of general scientific knowledge, synthesis, generalization of qualitative information, based objectively on  dialectical unity with natural and special sciences, primarily engineering and construction, relating to the object of statistical research, and mathematical, concerning the methodological aspects of obtaining quantitative estimates of the statistical indicators.In the statistics of living standards of the population, considerable attention is paid to the level of consumer spending of households. These are, directly, monetary expenses per capita, specific indicators of retail trade turnover and payment for services. However, only the statistics of the primary market and the characteristics of the creation of new facilities can show the participation of the population in the financing of the growth of national wealth, that part of it, which is determined by the international methodology, as the accumulated property created by the work of current and previous generations.It should be noted that the statistical analysis of the primary real estate market and the complex processes of creating objects that turn on it, is associated with a certain Russian paradox: a large-scale information attack, which is subjected to the domestic society, says about the reduction in recent years the standard of living of the population on various parameters, including the range and quantity of food consumption; at the same time, the volume of the area entered and realized in the primary real estate market, exactly, as well as the prices for it, grow uncontrollably that indicates inexhaustible solvent demand of the population for the acquired objects of long-term use.Results. In the research paper the information sources are ordered, the blocks of statistical indicators are consistently built, allowing to obtain both primary and generalized characteristics of the commissioning of primary objects related to both housing directly and to communication facilities that provide residential functionality of the results of construction and the entire residential infrastructure.Conclusion. The article deals with the analytical potential of indicators along with the prospects of their further application and the possibility of further improvement of statistical methodology and improving the quality of research of such a complex object as the primary real estate market.